Examining the associations between emotion regulation difficulties, anxiety, and eating disorder severity among inpatients with anorexia nervosa - Haynos, Ann F. (Compr Psychiatry, 2015)
OBJECTIVE: There is growing interest in the role of emotion regulation in anorexia nervosa (AN). Although anxiety is also hypothesized to impact symptoms of AN, little is known about how emotion regulation, anxiety, and eating disorder symptoms interact in AN. In this study, we examined the associations between emotion regulation, anxiety, and eating disorder symptom severity in AN. METHODS: Questionnaires and interviews assessing emotion regulation difficulties, anxiety, eating disorder symptoms, and eating disorder-related clinical impairment were collected from group of underweight individuals with AN (n = 59) at admission to inpatient treatment. Hierarchical linear regressions were used to examine the associations of emotion regulation difficulties, anxiety, and the interaction of these constructs with eating disorder symptoms and eating disorder-related clinical impairment. RESULTS: Emotion regulation difficulties were significantly positively associated with eating disorder symptoms and related clinical impairment only when anxiety levels were low and anxiety was significantly positively associated with eating disorder symptoms and related clinical impairment only when emotion regulation problems were not elevated. CONCLUSIONS: This study adds to a growing literature suggesting that emotion regulation deficits are associated with eating disorder symptoms in AN. Certain individuals with AN may especially benefit from a focus on developing emotion regulation skills in the acute stages of illness.